184k views
4 votes
Complete the following statement: f(3)=_____

Complete the following statement: f(3)=_____-example-1
User Kab Agouda
by
5.0k points

1 Answer

6 votes
Using this equation, f(3) = 23.

In order to find the value of f(3), we need to take the f(x) equation and put 3 everywhere we see x. Then we follow the order of operations to solve. So, let's start with the original.

f(x) = 2x^2 + 5sqrt(x - 2)

Now place 3 in for each x.

f(3) = 2(3)^2 + 5sqrt(3 - 2)

Now square the 3.

f(3) = 2(9) + 5 sqrt(3 - 2)

Do the subtraction inside of the parenthesis.

f(3) = 2(9) + 5sqrt(1)

Take the square root

f(3) = 2(9) + 5(1)

Multiply.

f(3) = 18 + 5

And add.

f(3) = 23
User Postfuturist
by
5.3k points